An ongoing WE: A focused ethnographic study of the relationship between child and hospital clown during recurrent pain‐related procedures and conditions. Issue 1 (22nd August 2019) - Kristensen, Helle Nygaard; Sørensen, Erik Elgaard; Stinson, Jennifer; Haslund‐Thomsen, Helle
Abstract: Aim: This study explored the interaction between child and hospital clown during recurrent hospitalizations for repeated pain‐related procedures and conditions. Background: Despite improvements in the management of pain in hospitalized children, procedural pain in particular is a common experience for hospitalized children, and they continue to report undertreated pain. Hospital clowns are widely used as a nonpharmacological intervention in hospitalized children. Little research has examined the influence of hospital clowns during recurrent hospitalizations on repeated painful procedures. Design and methods: Ethnographic fieldwork using focused ethnography was conducted. Data were collected during October–December 2017 using participant observation and informal interviews with children at one pediatric unit at a Danish university hospital. Data include 61 interactions between children aged 4–14 years and hospital clowns. The participants comprised 13 children undergoing recurrent hospitalizations. The data were coded using thematic analysis, and the research team verified the resulting themes. Results: The overarching theme was defined as An ongoing WE, based on two identified themes, that is, Stronger in a WE and Hope in the WE . The WE was characterized by a responsive interaction between the child and clown, which evolved over the course of an ongoing relationship. Conclusion: This study demonstrates how an ongoing WE was constructed with children during repeated painful procedures and conditions. Specifically, the study emphasizes the importance of developing a trusting relationship on the child's terms. Children seemed to experience enhanced coping with painful procedures during the recurring hospital clown encounters, thus reinforcing their competence and hope for coping with future painful procedures. These findings may improve psychosocial care for hospitalized children undergoing repeated painful procedures and conditions and may facilitate multidisciplinary initiatives, such as nurses' advocacy for the inclusion of hospital clowns during recurrent hospitalizations for repeated painful procedures to ensure optimal pain management.